Territorial Planning Policy in Agriculture Sector; Justice Oriented Critics - Ali Reza Jannesary; Morteza Teimourian; Mohammad Sadiq Torabzadeh (سیاست نامه علم و فناوری, 2018)
Agriculture as an academic field, like the other majors of social life, needs appropriate planning approaches based on a spatial perspective into regional capacities as much as national interests. Therefore, in addition to economic growth, spatial perspective prohibits regional imbalance and injustice because the emergence of injustice weakens social stability. As one of the approaches in spatial planning, territorial planning considers growth of regional potentials to remove imbalance. But, its perception of justice as well as its theoretical sufficiency and clarity are subject to vagueness. This research, by qualitative research method, analyzes territorial planning from the perspective of essential elements of justice, showing how it suffers from some vagueness about justice. So, agricultural policy-makers should beware of these vague questions concerning justice.